2018
DOI: 10.1371/journal.pone.0200815
|View full text |Cite
|
Sign up to set email alerts
|

The scale-free nature of protein sequence space

Abstract: The sequence space of five protein superfamilies was investigated by constructing sequence networks. The nodes represent individual sequences, and two nodes are connected by an edge if the global sequence identity of two sequences exceeds a threshold. The networks were characterized by their degree distribution (number of nodes with a given number of neighbors) and by their fractal network dimension. Although the five protein families differed in sequence length, fold, and domain arrangement, their network pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…The scale‐free distribution of the number of neighbours of a protein sequence demonstrates the existence of a few hubs and a large number of loosely connected sequences, as found previously for five different protein families. The scaling exponent of the α/β‐hydrolase sequence network (γ = 1.4) is similar to other protein families which had scaling exponents between 1.1 and 1.3 . The members of the homologous family 1011 (annotated as ‘protease 2’ or ‘oligopeptidase B’) had the highest number of neighbours (Table S1) and thus formed the largest hub region of the α/β‐hydrolase network.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The scale‐free distribution of the number of neighbours of a protein sequence demonstrates the existence of a few hubs and a large number of loosely connected sequences, as found previously for five different protein families. The scaling exponent of the α/β‐hydrolase sequence network (γ = 1.4) is similar to other protein families which had scaling exponents between 1.1 and 1.3 . The members of the homologous family 1011 (annotated as ‘protease 2’ or ‘oligopeptidase B’) had the highest number of neighbours (Table S1) and thus formed the largest hub region of the α/β‐hydrolase network.…”
Section: Discussionsupporting
confidence: 54%
“…Linear regression was performed for n ≤ 80 resulting in a scaling exponent γ = 1.4 (Fig. ), which is similar to the values of γ between 1.1 and 1.3 determined previously for five different protein families . All sequences in the hub region, ( n ≥ 300) belong to a single homologous family, the protease 2 homologous family number 1011, which are Y‐type α/β‐hydrolases from the N‐terminal domain superfamily number 8 (Table S1).…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Previously, the analysis of protein sequence networks has demonstrated that in several protein families, a small number of sequences are densely connected to other sequences within hub regions, whereas a large number of sequences are rather loosely connected . In the current SDRED, sequences annotated as serine 3‐dehydrogenase or ADP‐glycero‐manno‐heptose‐6‐epimerase from Helicobacter pylori were among these hub sequences, since they had many neighboring sequences at a threshold of 95% pairwise sequence identity.…”
Section: Resultsmentioning
confidence: 97%
“…This alternative method is based on the hypothesis that ancestral proteins have higher thermal stability than those observed today, with the notion that environmental temperatures were higher in the Precambrian era as one possible explanation, although the origins of the stability and trends across evolutionary time are still under debate ( 84 ). Not directly related to stability is the method of identifying hub sequences for use as starting scaffolds ( 85 ). These sequences are highly connected to related sequences through mutational space.…”
Section: Future Directionsmentioning
confidence: 99%